Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the problem, we need to find the roots of the given quadratic equations and match them with their corresponding solution sets.
Let's begin by solving each quadratic equation step-by-step:
1. Solve [tex]\( a^2 - 9a + 14 = 0 \)[/tex]
This is in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex].
The solutions [tex]\( a \)[/tex] are given by the quadratic formula:
[tex]\[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For [tex]\( a^2 - 9a + 14 = 0 \)[/tex]:
[tex]\[ a = \frac{-(-9) \pm \sqrt{(-9)^2 - 4(1)(14)}}{2(1)} \][/tex]
[tex]\[ a = \frac{9 \pm \sqrt{81 - 56}}{2} \][/tex]
[tex]\[ a = \frac{9 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ a = \frac{9 \pm 5}{2} \][/tex]
So, the solutions are:
[tex]\[ a = \frac{9 + 5}{2} = 7 \quad \text{and} \quad a = \frac{9 - 5}{2} = 2 \][/tex]
Therefore, the solution set for [tex]\( a^2 - 9a + 14 = 0 \)[/tex] is [tex]\( \{7, 2\} \)[/tex].
2. Solve [tex]\( a^2 - 5a - 14 = 0 \)[/tex]
Again using the quadratic formula:
[tex]\[ a = \frac{-(-5) \pm \sqrt{(-5)^2 - 4(1)(-14)}}{2(1)} \][/tex]
[tex]\[ a = \frac{5 \pm \sqrt{25 + 56}}{2} \][/tex]
[tex]\[ a = \frac{5 \pm \sqrt{81}}{2} \][/tex]
[tex]\[ a = \frac{5 \pm 9}{2} \][/tex]
So, the solutions are:
[tex]\[ a = \frac{5 + 9}{2} = 7 \quad \text{and} \quad a = \frac{5 - 9}{2} = -2 \][/tex]
Therefore, the solution set for [tex]\( a^2 - 5a - 14 = 0 \)[/tex] is [tex]\( \{7, -2\} \)[/tex].
Now, let's match these solution sets with the given equations.
1. [tex]\( a^2 - 9a + 14 = \{2, 7\} \)[/tex]
2. [tex]\( a^2 - 5a - 14 = \{7, -2\} \)[/tex]
So, the final matching is:
- [tex]\( a^2 - 9a + 14 = 0 \)[/tex] matches with [tex]\( \{2, 7\} \)[/tex]
- [tex]\( a^2 - 5a - 14 = 0 \)[/tex] matches with [tex]\( \{7, -2\} \)[/tex]
Let's begin by solving each quadratic equation step-by-step:
1. Solve [tex]\( a^2 - 9a + 14 = 0 \)[/tex]
This is in the standard form [tex]\( ax^2 + bx + c = 0 \)[/tex].
The solutions [tex]\( a \)[/tex] are given by the quadratic formula:
[tex]\[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For [tex]\( a^2 - 9a + 14 = 0 \)[/tex]:
[tex]\[ a = \frac{-(-9) \pm \sqrt{(-9)^2 - 4(1)(14)}}{2(1)} \][/tex]
[tex]\[ a = \frac{9 \pm \sqrt{81 - 56}}{2} \][/tex]
[tex]\[ a = \frac{9 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ a = \frac{9 \pm 5}{2} \][/tex]
So, the solutions are:
[tex]\[ a = \frac{9 + 5}{2} = 7 \quad \text{and} \quad a = \frac{9 - 5}{2} = 2 \][/tex]
Therefore, the solution set for [tex]\( a^2 - 9a + 14 = 0 \)[/tex] is [tex]\( \{7, 2\} \)[/tex].
2. Solve [tex]\( a^2 - 5a - 14 = 0 \)[/tex]
Again using the quadratic formula:
[tex]\[ a = \frac{-(-5) \pm \sqrt{(-5)^2 - 4(1)(-14)}}{2(1)} \][/tex]
[tex]\[ a = \frac{5 \pm \sqrt{25 + 56}}{2} \][/tex]
[tex]\[ a = \frac{5 \pm \sqrt{81}}{2} \][/tex]
[tex]\[ a = \frac{5 \pm 9}{2} \][/tex]
So, the solutions are:
[tex]\[ a = \frac{5 + 9}{2} = 7 \quad \text{and} \quad a = \frac{5 - 9}{2} = -2 \][/tex]
Therefore, the solution set for [tex]\( a^2 - 5a - 14 = 0 \)[/tex] is [tex]\( \{7, -2\} \)[/tex].
Now, let's match these solution sets with the given equations.
1. [tex]\( a^2 - 9a + 14 = \{2, 7\} \)[/tex]
2. [tex]\( a^2 - 5a - 14 = \{7, -2\} \)[/tex]
So, the final matching is:
- [tex]\( a^2 - 9a + 14 = 0 \)[/tex] matches with [tex]\( \{2, 7\} \)[/tex]
- [tex]\( a^2 - 5a - 14 = 0 \)[/tex] matches with [tex]\( \{7, -2\} \)[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.